Near-IR aza-BODIPY-based probe for the selective simultaneous detection of Cu2+ in aqueous buffer solutions and its application in biological samples - Panida Praikaew (2020)
© 2020 Elsevier B.V. On the basis of an aza-BODIPY core, a near-IR BDT probe was designed for Cu2+ detection. The Cu2+ sensing ability of the BDT probe demonstrated absorbance and fluorescence signals in near-IR regions. The probe capably detected Cu2+ with high sensitivity and selectivity in aqueous buffer solutions with a low detection limit of 3.75 ppb which is lower than the acceptable drinking water concentration specified by the U.S. Environmental Protection Agency and World Health Organization. The sensing ability of the probe also increased selectivity to Cu2+ over Hg2+ by adding cysteine as an auxiliary reagent. The binding of BDT-Cu2+ was proven to be 2:1 via molecular modeling and Job's plot analysis. Interestingly, the BDT probe exhibited outstanding chromogenic and luminescent change in the presence of only Cu2+ and could detect Cu2+ in HepG2 cells as a biological sample.